2013
DOI: 10.1186/1472-6963-13-511
|View full text |Cite
|
Sign up to set email alerts
|

MOVE: weight management program across the veterans health administration: patient- and facility-level predictors of utilization

Abstract: BackgroundHealth care systems initiating major behavioral health programs often face challenges with variable implementation and uneven patient engagement. One large health care system, Veterans Health Administration (VHA), recently initiated the MOVE!® Weight Management Program, but it is unclear if veterans most in need of MOVE!® services are accessing them. The purpose of this study was to examine patient and facility factors associated with MOVE!® utilization (defined as 1 or more visits) across all VHA fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 15 publications
0
11
0
Order By: Relevance
“…Prior work indicated that only 2% to 12% of eligible veterans participate in MOVE!, and weight change associated with MOVE! is modest (mean loss of 0.13‐3.3 kg) .…”
Section: Introductionmentioning
confidence: 98%
“…Prior work indicated that only 2% to 12% of eligible veterans participate in MOVE!, and weight change associated with MOVE! is modest (mean loss of 0.13‐3.3 kg) .…”
Section: Introductionmentioning
confidence: 98%
“…Participation is less than 5% of eligible veterans, 6 average weight loss is minimal, 1-2 pounds, 6 and MOVE is more likely to be utilized by those with a body mass index (BMI) above 30, indicating obesity. [6][7][8] Since people with SMI often have cognitive deficits, limited literacy, and challenging social situations, interventions need to be tailored for this population. Individual-and group-based behavioral interventions tailored for SMI have repeatedly been shown to result in weight reduction, [9][10][11][12][13][14][15] though a recent study showed no benefit of intervention.…”
Section: Introductionmentioning
confidence: 99%
“…Only 5% to 10% of eligible veterans opt to participate in the MOVE! program . Prior studies have shown that these patients are more likely to be women, unmarried, and younger and are more likely to have a higher baseline BMI .…”
Section: Discussionmentioning
confidence: 99%
“…Although more than 95% of eligible veterans are offered the MOVE! program each year, only 5% to 10% opt to participate, and the noncompletion rate is estimated to be as high as 74%, further stressing the importance of understanding and encouraging continued engagement after recruitment . When participants do complete the program, they see long‐term improvements in weight loss, diabetes, and hyperlipidemia .…”
Section: Introductionmentioning
confidence: 99%